Biomechanical comparison of a less invasive technique and the current accepted technique for arthrodesis of the equine proximal interphalangeal joint - Bras, Jose J. (Kansas State University, 2010)
Objective - To compare the biomechanical characteristics of the currently recommended (CR) technique and a less invasive (LI) surgical approach for arthrodesis of the proximal interphalangeal joint (PIPJ). Additionally, to describe a technique for cartilage removal and disruption of the subchondral bone. Study design - Randomized paired limb design for biomechanical comparison. Cartilage removal and subchondral bone disruption was accomplished using an orthopedic drill bit. Sample Population – 76 cadaver limbs. Methods - Cadaver PIPJs were drilled using a 3.5mm, 4.5mm or 5.5mm drill bit. Articular surfaces were digitally photographed and analyzed. Other paired PIPJs were arthrodesed using either the CR or the LI surgical technique. Implants consisted of a 3-hole DCP and two 5.5mm transarticular screws. Constructs were tested to failure in dorso-palmar/plantar and latero-medial in single cycle 3-point bending. The maximum load and yield load was measured and composite stiffness was calculated and statistically compared. Results - The LI technique had significantly greater mean yield load (11.3 ± 2.8 kN vs. 7.68 ± 1.1 kN, P=0.008) and mean maximum load (13.5 ± 3.1 kN vs. 10.1 ± 1.94 kN, P= 0.02) under latero-medial bending. Under dorso-palmar/plantar bending there was no statistical difference between the surgical approaches (P=0.5). The 4.5mm drill bit removed 42% ± 7.3 of the cartilage and disrupted subchondral bone. The LI technique had a decreased surgical time (19 ± 3 min.) when compared with the CR (31 ± 3 min.) technique. Conclusion – The LI technique results in a stronger composite as measured in 3-point bending, loaded to failure. Clinical Relevance – The LI surgical technique may be considered for clinical cases requiring arthrodesis of the PIPJ as there is no reduction in composite strength.
Keywords: Proximal interphalangeal joint; Less invasive surgical technique; Pastern arthrodesis; Biomechanical comparison; Agriculture, Animal Pathology (0476)